Self‐Assembled Perovskite Nanoislands on CH3NH3PbI3 Cuboid Single Crystals by Energetic Surface Engineering. (12th September 2021) - Zhang, Yurou; Kim, Dohyung; Yun, Jung‐Ho; Lim, Jongchul; Jung, Min‐Cherl; Wen, Xiaoming; Seidel, Jan; Choi, Eunyoung; Xiao, Mu; Qiu, Tengfei; Lyu, Miaoqiang; Han, EQ; et al.
Abstract: Organometal perovskite single crystals have been recognized as a promising platform for high‐performance optoelectronic devices, featuring high crystallinity and stability. However, a high trap density and structural nonuniformity at the surface have been major barriers to the progress of single crystal‐based optoelectronic devices. Here, the formation of a unique nanoisland structure is reported at the surface of the facet‐controlled cuboid MAPbI3 (MA = CH3 NH3 + ) single crystals through a cation interdiffusion process enabled by energetically vaporized CsI. The interdiffusion of mobile ions between the bulk and the surface is triggered by thermally activated CsI vapor, which reconstructs the surface that is rich in MA and CsI with reduced dangling bonds. Simultaneously, an array of Cs‐Pb‐rich nanoislands is constructed on the surface of the MAPbI3 single crystals. This newly reconstructed nanoisland surface enhances the light absorbance over 50% and increases the charge carrier mobility from 56 to 93 cm 2 V −1 s −1 . As confirmed by Kelvin probe force microscopy, the nanoislands form a gradient band bending that prevents recombination of excess carriers, and thus, enhances lateral carrier transport properties. This unique engineering of the single crystal surface provides a pathway towards developing high‐quality perovskite single‐crystal surface for optoelectronic applications. Abstract : To restructure nonuniform CH3 NH3 PbI3 perovskite crystal surfaces, an effective surface engineering strategy is successfully demonstrated. By thermally evaporating energetic CsI on single‐crystal surfaces, a unique nanoisland structure is formed through a cation interdiffusion process. This morphology induces a gradient band bending, which increases the charge carrier mobility from 56 to 93 cm 2  V −1  s −1 .